Komunikasi Pemasaran pada PT. Jasaraharja Putera Tentang Aplikasi EZurance - Okvita Maharani Putri; Muhammad Noor Hidayat (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
Along with the progress of digitalization in Indonesia, it encourages business actors or industries to innovate digitally. PT. Jasaraharja is one of the state-owned companies engaged in general insurance, one of which is motor vehicle insurance (JP-Astor). In line with the vision of PT. Jasaraharja Putera, the company wants to become a leading insurance company in Indonesia, therefore the company continues to encourage the development of innovation as part of its efforts to continue to increase competitiveness and provide adaptive services to the needs of modern society. This study aims to determine the marketing communication strategy carried out by PT. Jasaraharja Putera Semarang Branch to market an application-based insurance product called EZurance. The method used in this study is descriptive qualitative. Data collection techniques use interviews and observations. The results of this study determine the marketing communication of PT. Jasaraharja Putera Semarang Branch through direct and indirect marketing communications. The purpose of this study is to ensure that the marketing communications used run effectively and efficiently in accordance with the company's expectations.